Combination of Pragmatic and Constitutive Environmental Communication of Dayak Wehea Tribe in Nature Conservation Efforts - Fajaria Menur Widowati; Maulina Pia Wulandari (Indonesian Journal of Environment and Sustainable Development, 2022)
This research aims to determine the environmental communication conducted by the citizen of the Dayak Wehea Tribe in Nehas Liah bing Village, East Kutai, East Kalimantan, which is a society that lives around the forest and relies on the forest as a source of life and also has local knowledge about how to relate to the nature, and other creatures, which must intersect with modern development that enters the territory of the Dayak Wehea tribe and how it causes social changes. This research was conducted with an ethnographic communication method to examine the community of speech, language, culture, and rituals. Data were collected by observation, in-depth interviews, and document analysis of archival, textual, or visual data obtained from the field research. We conclude that the Wehea Dayak Tribe combines pragmatic and constitutive environmental communication, which is seen in the management of the protected forest of Wehea and the series of paddy rituals (Lom Plai). The results of this research explain that the two communication models as an effort to preserve the environment cannot be separated if we want to increase the participation and involvement of group members and the citizen in general. Keywords: Environmental communication, ritual communication, environmental conservation, Lom Plai, Dayak Wehea tribe